Integrated eicosanoid lipidomics and gene expression reveal decreased prostaglandin catabolism and increased 5‐lipoxygenase expression in aggressive subtypes of endometrial cancer. Issue 1 (27th November 2018) - Cummings, Michele; Massey, Karen A; Mappa, Georgia; Wilkinson, Nafisa; Hutson, Richard; Munot, Sarika; Saidi, Sam; Nugent, David; Broadhead, Timothy; Wright, Alexander I; Barber, Stuart; Nicolaou, Anna; et al.
Abstract: Eicosanoids comprise a diverse group of bioactive lipids which orchestrate inflammation, immunity, and tissue homeostasis, and whose dysregulation has been implicated in carcinogenesis. Among the various eicosanoid metabolic pathways, studies of their role in endometrial cancer (EC) have very much been confined to the COX‐2 pathway. This study aimed to determine changes in epithelial eicosanoid metabolic gene expression in endometrial carcinogenesis; to integrate these with eicosanoid profiles in matched clinical specimens; and, finally, to investigate the prognostic value of candidate eicosanoid metabolic enzymes. Eicosanoids and related mediators were profiled using liquid chromatography–tandem mass spectrometry in fresh frozen normal, hyperplastic, and cancerous (types I and II) endometrial specimens ( n  = 192). Sample‐matched epithelia were isolated by laser capture microdissection and whole genome expression analysis was performed using microarrays. Integration of eicosanoid and gene expression data showed that the accepted paradigm of increased COX‐2‐mediated prostaglandin production does not apply in EC carcinogenesis. Instead, there was evidence for decreased PGE2 /PGF2α inactivation via 15‐hydroxyprostaglandin dehydrogenase (HPGD) in type II ECs. Increased expression of 5‐lipoxygenase ( ALOX5 ) mRNA was also identified in type II ECs, together with proportional increases in its product, 5‐hydroxyeicosatetraenoic acid (5‐HETE). Decreased HPGD and elevated ALOX5 mRNA expression were associated with adverse outcome, which was confirmed by immunohistochemical tissue microarray analysis of an independent series of EC specimens ( n  = 419). While neither COX‐1 nor COX‐2 protein expression had prognostic value, low HPGD combined with high ALOX5 expression was associated with the worst overall and progression‐free survival. These findings highlight HPGD and ALOX5 as potential therapeutic targets in aggressive EC subtypes. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.